The Interplay of Self-Confidence and Communicative Competence of Junior High School in Indonesia - Hasan, Hasan; Sadapotto, Andi; Hanafi, Muhammad; Iksan, Muhammad (Maspul Journal of English Studies, 2022)
This Article aims to describe whether there is the interplay of self confidance and communicative competence of junior high school where the students of SMP 9 Pinrang is as place to apply research. This research uses cluster sumpling method and oral test. The population in this research is the students of class VII SMPN 9 Pinrang. The total population is 104 students. The sample used is class VIIL.1 amounted to 28 students. The method used in the assessment of speech is an oral test. Result of research by using Pearson Product Moment obtained r value count 0,700 and with value of product r product moment product with N = 28 found 0,478 at significant level 1% and found 0,374 at level signifikan5%. And to know the level of product moment correlation then coefficient 0.61-0.80 = substantial.Thus it can be interpreted to the rxy that between variable X and variable Y. It can be seen on the analysis result that is: 0,700> 0,478 (5%) and 0,700 0,374 (1%) with d.b:28. This means Ho is rejected and Ha accepted. The conclusion in this study is there is a significant relationship between student self-confidence and speaking ability of eight-year students SMPN 9 Pinrang.